Association of ACP1 genotypes and clinical parameters in patients with metabolic syndrome - AKKİPRİK, MUSTAFA; ÖZER, SIDIKA AYŞE (TUBITAK SCIENTIFIC & TECHNICAL RESEARCH COUNCIL TURKEY, 2011)
Aim: Acid phosphatase locus 1 (ACP1) encodes a polymorphic enzyme and has potential implications for the development of metabolic syndrome (MS) by altering insulin sensitivity. The aim of this study was to determine whether a relationship exists between ACP1 genotypes and various metabolic syndrome risk factors. Materials and methods: We employed a PCR-RFLP based genotyping of ACP1 in a cohort of 70 patients with MS and 168 healthy individuals. Results: When compared to controls, genotypes associated with low enzyme activity were observed at significantly lower frequencies in both sexes. Of note, high enzyme activity genotypes were more common in patients with MS when compared with medium and low enzyme activity genotypes. *A allele frequency was not different between patients and controls even considering sex; however, there was a good correlation of the presence of the allele with body composition, serum cortisol levels and suppressibility of cortisol, particularly in women with MS. Conclusion: Our findings suggest that low enzyme activity genotypes seem to be associated with a protective effect for the development of MS. Additionally, *A allele carriage affects body composition in women but not in men, and the presence of this allele might modulate serum cortisol levels as well as its suppressibility in both sexes, in an inverse manner.
Keywords: Metabolic syndrome; ACP1 genotype; clinical variables; cortisol; CELL ACID-PHOSPHATASE; PROTEIN-TYROSINE-PHOSPHATASE; GENE; POLYMORPHISM; CHOLESTEROL; EXPRESSION; CORTISOL